Peran Orang Tua dalam Menumbuhkan Minat dan Motivasi Anak Mempelajari Ilmu Fiqih di TPA Hasan Al-Hanafiyah - Ansharuddin M; Silawati (PT. Pusmedia Group Indonesia, 2023)
Parents are the people who play the most important role in the growth and development of children, especially in the world of education. In the world of education, there are three things that support the achievement of educational goals. The education in question is formal, non-formal and informal education. Of the three supports for children's education, the most influential is informal education, where parents and families are the factors that will determine the character of a child so that they can become a quality generation. The discussion in this study is the role of parents in fostering children's interest and motivation to learn fiqh at TPA Hasan Al-Hanafiyah Bakung Hamlet, Suwari Village. With a discussion that focuses on 1). How do parents support their children in learning fiqh at TPA Hasan AL-Hanafiyah Bakung Hamlet, Suwari Village. 2). How do parents foster children's interest in learning fiqh at TPA Hasan Al-Hanafiyah Bakung Hamlet Suwari Village. 3). How do parents motivate children to learn fiqh at TPA Hasan Al-Hanafiyah Bakung Hamlet, Suwari Village. The research method used is qualitative research method, and for the data collection process using observation, interview and documentation techniques. While for data analysis using triangulation techniques. The results of the study showed that: a) the role of parents in supporting children to learn fiqh is very important considering that parents play a role as educators, protectors, mentors and discipline enforcers; b) the way parents foster children's interest is by encouraging them to learn fiqh. The way parents foster children's interests by providing encouragement, supervision and control so that children's interests can be directed clearly; c) the way parents motivate children is to provide encouragement, direction and help children to be enthusiastic in studying fiqh. Keywords: Role of Parents; Interest and Motivation; Learning Fiqh Science.